2004
DOI: 10.1515/cclm.2004.108
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac natriuretic hormones, neuro-hormones, thyroid hormones and cytokines in normal subjects and patients with heart failure

Abstract: The derangement of neuro-endocrine control of circulation influences both disease evolution and response to treatment in patients with heart failure, but little data are available about the complex relationships between the degree of neuro-hormonal activation and clinical severity. We studied the relationships between cardiac natriuretic hormones (CNHs) and several neuro-hormones and immunological markers in a prospective cohort of 105 consecutive patients with cardiomyopathy (77 men and 28 women, mean age 66.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
67
0
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(73 citation statements)
references
References 55 publications
3
67
0
3
Order By: Relevance
“…The association between impaired NYHA class and increased NP levels is in accordance with studies on acquired heart disease, as well as with a small series of congenital heart disease [8][9][10].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The association between impaired NYHA class and increased NP levels is in accordance with studies on acquired heart disease, as well as with a small series of congenital heart disease [8][9][10].…”
Section: Discussionsupporting
confidence: 88%
“…In patients with unchanged NYHA class (n = 26) or ventricular function (n = 21), the natriuretic peptide concentration could go in any direction, and in those with improved ventricular function (n = 12) or functional status (n = 6), neurohormone concentrations generally did not diminish. Other arbitrary cut-off values (10,30 and 40%) were also tested during initial modelling of the data, but this did not improve the discriminatory value of the test. However, higher cut-offs severely reduced the number of patients in whom natriuretic peptide levels changed significantly.…”
Section: Predictive Value Of Np and Correlation Of Changes In Np To Cmentioning
confidence: 99%
“…They observed secondary T 3 hypothyroidism and a marked PRA elevation in these patients but no significant change in ADH or aldosterone, indicating a dissociation of the renin-angiotensin-aldosterone mechanism in brain-dead patients. Emdin et al (2004) also reported that PRA and aldosterone levels were significantly higher in heart failure patients than in healthy subjects and showed a significant linear increase from controls through to patients with severe heart failure, while T 3 and FT 3 levels were significantly decreased in heart failure patients. However, subsequent studies reported normal PRA and aldosterone values in heart failure patients (Pingitore et al 2008, Fontana et al 2012, and Pingitore et al (2008) found a significant decrease in plasma aldosterone but no change in PRA after T 3 infusion.…”
Section: New Ras Componentsmentioning
confidence: 85%
“…on average, only an increment of about 50-folds) ( Figure 1 and Table 2), measured by an immunoradiometric assay (IRMA) [5,6]. Of course, the ratio between NTproBNP and BNP is greatly method dependent [5][6][7][8]; as a The plasma concentration values of NT-proBNP, measured by the ECLIA method (Roche Diagnostics, Germany), and BNP, measured by the immunoradiometric assay (IRMA) Shionoria (Shionogi &Co, Japan), are expressed as the ratio between the mean biomarker concentration values found in HF groups and that found in healthy control subjects. Original BNP and NT-proBNP values measured in healthy subjects and patients with heart failure are reported in Table 2 and were previously discussed in detail by Prontera et al [2].…”
Section: Analytical Characteristics Of Bnp and Nt-probnp Methodsmentioning
confidence: 99%